Empowering Students for the Data-Driven World: A Qualitative Study of the Relevance of Learning about Data-Driven Technologies - Höper, Lukas; Schulte, Carsten (Informatics in Education)
In K-12 computing education, there is a need to identify and teach concepts that are relevant to understanding machine learning technologies. Studies of teaching approaches often evaluate whether students have learned the concepts. However, scant research has examined whether such concepts support understanding digital artefacts from everyday life and developing agency in a digital world. This paper presents a qualitative study that explores students’ perspectives on the relevance of learning concepts of data-driven technologies for navigating the digital world. The underlying approach of the study is data awareness, which aims to support students in understanding and reflecting on such technologies to develop agency in a data-driven world. This approach teaches students an explanatory model encompassing several concepts of the role of data in data-driven technologies. We developed an intervention and conducted retrospective interviews with students. Findings from the analysis of the interviews indicate that students can analyse and understand data-driven technologies from their everyday lives according to the central role of data. In addition, students’ answers revealed four areas of how learning about data-driven technologies becomes relevant to them. The paper concludes with a preliminary model suggesting how computing education can make concepts of data-driven technologies meaningful for students to understand and navigate the digital world.
Keywords: Computer Science Applications; Communication; Education; General Engineering

ARIadne – An Explanation Model for Digital Artefacts - Winkelnkemper, Felix; Höper, Lukas; Schulte, Carsten (Informatics in Education)
When it comes to mastering the digital world, the education system is more and more facing the task of making students competent and self-determined agents when interacting with digital artefacts. This task often falls to computing education. In the traditional fields of computing education, a plethora of models, guidelines, and principles exist, which help scholars and teachers identify what the relevant aspects are and which of them one should cover in the classroom. When it comes to explaining the world of digital artefacts, however, there is hardly any such guiding model. The ARIadne model introduced in this paper provides a means of explanation and exploration of digital artefacts which help teachers and students to do a subject analysis of digital artefacts by scrutinizing them from several perspectives. Instead of artificially separating aspects which target the same phenomena within different areas of education (like computing, ICT or media education), the model integrates technological aspects of digital artefacts and the relevant societal discourses of their usage, their impacts and the reasons behind their development into a coherent explanation model.
Keywords: Computer Science Applications; Communication; Education; General Engineering

A new algorithmic imaginary - Schulz, Christian (Media, Culture & Society)
The algorithmic imaginary as a theoretical concept has received increasing attention in recent years as it aims at users’ appropriation of algorithmic processes operating in opacity. But the concept originally only starts from the users’ point of view, while the processes on the platforms’ side are largely left out. In contrast, this paper argues that what is true for users is also valid for algorithmic processes and the designers behind. On the one hand, the algorithm imagines users’ future behavior via machine learning, which is supposed to predict all their future actions. On the other hand, the designers anticipate different actions that could potentially performed by users with every new implementation of features such as social media feeds. In order to bring into view this permanently reciprocal interplay coupled to the imaginary, in which not only the users are involved, I will argue for a more comprehensive and theoretically precise algorithmic imaginary referring to the theory of Cornelius Castoriadis. In such a perspective, an important contribution can be formulated for a theory of social media platforms that goes beyond praxeocentrism or structural determinism.
Keywords: Sociology and Political Science; Communication

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Voices in Dialogue: Taking Polyphony in Academic Writing Seriously - Karsten, Andrea (Written Communication)
In the past decades, the notion of voice in the theorizing and teaching of academic writing has been the subject of much debate and conceptual change, especially concerning its relation to writer identity. Many newer accounts of voice and identity in academic writing draw on the dialogical concept of voice by Bakhtin. However, some theoretical and methodological inconsistencies have surfaced in the adaptions of the concept. Working from a refinement of the dialogical notion of voice based on the concepts of polyphony and interiorization, this article presents a methodological approach for analyzing voice(s) in writing. The article presents material around the evolution of an early-career researcher’s dissertation synopsis. The material is multilayered, including the writer’s text, transcripts from an interdisciplinary peer-feedback conversation with two colleagues, and a video-stimulated interview with the writer. Excerpts of the material were analyzed to trace the polyphony of interiorized voices that influenced the writing. This focus revealed the multivoicedness of academic texts as an effect of their history of coming into being. This article contributes to the question of voice and identity in academic writing from a dialogical psycholinguistic perspective by presenting a de-reifying notion of voice grounded in an understanding of writing as a polyphonic activity, which also feeds into the formation of a writer’s self.
Keywords: Literature and Literary Theory; Communication

Rekonstruktive Evaluationsforschung im Kontext praxeologischer Kompetenzdiskurse. Kritische Reflexionen und konzeptionelle Überlegungen zur Dokumentarischen Evaluationsforschung - Bloh, Thiemo (Zeitschrift für Evaluation)
Praxeologische Kompetenzansätze verstehen Kompetenz als sozial erlernt und folglich als relativ zum sozialen Kontext. Damit einher geht die Frage, wie solche praxeologisch gerahmten Kompetenzen eigentlich unabhängig von der sie hervorbringenden Praxis evaluiert werden können – und eben dadurch erst für einen breiteren Kompetenzdiskurs fruchtbar sind. Die Dokumentarische Evaluationsforschung bietet hierzu erste Anhaltspunkte, offenbart aber auch Grenzen, die mit dem Evaluationsverständnis zusammenhängen, sich jedoch in der Forschungspraxis so nicht finden lassen. Aus der Differenz zwischen Methode und Praxis dokumentarischer Evaluation lässt sich formulieren, wie eine praxeologische Evaluation gestaltet werden könnte. Dabei spielt die Formulierung von Referenzrahmen eine zentrale Rolle, welche einerseits der zu evaluierenden Praktik external sein, andererseits praktisch formuliert werden müssen, damit sie soziale Praktiken jenseits ihrer eigenen Sinnhaftigkeit evaluativ (er-)fassen können.
Keywords: Strategy and Management; Applied Psychology; Social Sciences (miscellaneous); Education; Communication; Statistics and Probability

How News Websites Refer to Twitter: A Content Analysis of Twitter Sources in Journalism - Kapidzic, Sanja; Neuberger, Christoph; Frey, Felix; Stieglitz, Stefan; Mirbabaie, Milad (Journalism Studies)
Keywords: Communication

Which “motionese” parameters change with children's age? Disentangling attention-getting from action-structuring modifications - Rohlfing, Katharina; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta (Frontiers in Communication)
Modified action demonstration—dubbed motionese— has been proposed as a way to help children recognize the structure and meaning of actions. However, until now, it has been investigated only in young infants. This brief research report presents findings from a cross-sectional study of parental action demonstrations to three groups of 8–11, 12–23, and 24–30-month-old children that applied seven motionese parameters; a second study investigated the youngest group of participants longitudinally to corroborate the cross-sectional results. Results of both studies suggested that four motionese parameters (Motion Pauses, Pace, Velocity, Acceleration) seem to structure the action by organizing it in motion pauses. Whereas these parameters persist over different ages, three other parameters (Demonstration Length, Roundness, and Range) occur predominantly in the younger group and seem to serve to organize infants' attention on the basis of movement. Results are discussed in terms of facilitative vs. pedagogical learning.
Keywords: Social Sciences (miscellaneous); Communication

Computers and Education – Recognising Opportunities and Managing Challenges - Passey, Don; Brinda, Torsten; Cornu, Bernard; Holvikivi, Jaana; Lewin, Cathy; Magenheim, Johannes; Morel, Raymond; Osorio, Javier; Tatnall, Arthur; Thompson, Barrie; Webb, Mary (Advancing Research in Information and Communication Technology)
Keywords: Educational technologies; Education and technologies; Digital technologies and education; Information technologies; Communication technologies; Educational technologies and research; Educational technologies and pedagogical practices; Educational technologies and policy; Educational management and technologies; Professional development and educational technologies

SLA-controlled Proxy Service Through Customisable MANO Supporting Operator Policies - Soenen, Thomas; Vicens, Felipe; Bonnet, José; Parada, Carlos; Kapassa, Evgenia; Touloupou, Marious; Fotopulou, Eleni; Zafeiropoulos, Anastasios; Pol, Ana; Kolometsos, Stavros; Xilouris, George; Alemany, Pol; et al. (2019 IFIP/IEEE Symposium on Integrated Network and Service Management (IM))
Service Level Agreements are essential tools enabling clients and telco operators to specify required quality of service. The 5GTANGO NFV platform enables SLAs through policies and custom service lifecycle management components. This allows the operator to trigger certain lifecycle management events for a service, and the network service developer to define how to execute such events (e.g., how to scale). In this demo we will demonstrate this unique 5GTANGO concept using an elastic proxy service supported by a high availability SLA enforced through a range of traffic regimes.
Keywords: 5G mobile communication; contracts; quality of service; telecommunication traffic; virtualisation; custom service lifecycle management components; lifecycle management events; network service developer; elastic proxy service; SLA-controlled proxy service; customisable MANO; operator policies; Service Level Agreements; unique 5G TANGO concept; 5G TANGO NFV platform; quality of service; traffic regimes; high availability SLA; Monitoring; Probes; Portals; Quality of service; Tools; Servers; Graphical user interfaces

The network ROI - Khan, Gohar; Mohaisen, Manar; Trier, Matthias (Internet Research)
Purpose Leveraging social action theory, social network theory and the notion of network externality, the purpose of this paper is to model two different return on investment (ROI) measures: the networked ROI which captures the network effect originating from a social media investment, and the discrete ROI which focuses social media discrete returns from individual users. Design/methodology/approach A field experiment was set up over a period of three months to test the effects of two variants of an advertisement campaign (a social vs a discrete ad) on the modeled networked and discrete ROIs. Findings The authors find that emphasizing discrete user actions leads to lower network gains, but higher monetary returns while the social action emphasis produces higher network gains, but lower monetary returns. The study further suggests that social action focus is preferable for brand promotion and engagement, whereas the discrete action focus is suitable for boosting sales and website traffic. Practical implications Several potential implications for social media researchers and marketers are also discussed. Originality/value The authors for the first time showed that that the social media returns are derived not only from individual actions taken by the user (e.g. likes and shares) but also from users’ social interdependencies and the additional exposure that results from network effects.
Keywords: Economics and Econometrics; Sociology and Political Science; Communication

Interactionism in the age of ubiquitous telecommunication - Klowait, Nils (Information, Communication & Society)
Keywords: Library and Information Sciences; Communication

Acoustic Microphone Geometry Calibration: An overview and experimental evaluation of state-of-the-art algorithms - Plinge, Axel; Jacob, Florian; Haeb-Umbach, Reinhold; Fink, Gernot A. (IEEE Signal Processing Magazine)
Today, we are often surrounded by devices with one or more microphones, such as smartphones, laptops, and wireless microphones. If they are part of an acoustic sensor network, their distribution in the environment can be beneficially exploited for various speech processing tasks. However, applications like speaker localization, speaker tracking, and speech enhancement by beamforming avail themselves of the geometrical configuration of the sensors. Therefore, acoustic microphone geometry calibration has recently become a very active field of research. This article provides an application-oriented, comprehensive survey of existing methods for microphone position self-calibration, which will be categorized by the measurements they use and the scenarios they can calibrate. Selected methods will be evaluated comparatively with real-world recordings.
Keywords: Acoustic sensors; Microphones; Portable computers; Smart phones; Wireless communication; Wireless sensor networks

Studying the Co-Construction of Interaction Protocols in Collaborative Tasks with Humans - Vollmer, Anna-Lisa; Grizou, Jonathan; Lopes, Manuel; Rohlfing, Katharina; Oudeyer, Pierre-Yves (2014 Joint IEEE International Conference on Development and Learning and on Epigenetic Robotics)
Keywords: interaction; communication; co-construction; interaction protocols

Influence and Dissemination Of Sentiments in Social Network Communication Patterns - Hillmann, Robert; Trier, Matthias (ECIS 2013 Proceedings)
Previous research suggests the existence of sentiments in online social networks. In comparison to real life human interaction, in which sentiments have been shown to have an influence on human behaviour, it is not yet completely understood which mechanisms explain how sentiments influence users in online environments. We develop a theoretical framework that tries to bridge the gap between social influence theories that focus on offline interactions on one hand and online interaction in social networks on the other hand. We then test our hypothesis about the influence and dissemination of sentiments in a quantitative analysis that is based on retrieved textual messages of communication patterns in over 12000 online social networks. Our empirical results suggest a general influence of sentiments on node communication patterns that is evidenced by increased occurrences of subsequent messages that express the same sentiment polarization. We interpret these findings and suggest future research to advance our currently limited theories that assume perceived and generalized social influence to path-dependent social influence models that consider actual behaviour.
Keywords: Social Network Analysis; Sentiment Analysis; Communication Patterns

Mindful tutors: Linguistic choice and action demonstration in speech to infants and a simulated robot - Fischer, Kerstin; Foth, Kilian; Rohlfing, Katharina; Wrede, Britta (Interaction Studies)
It has been proposed that the design of robots might benefit from interactions that are similar to caregiver–child interactions, which is tailored to children’s respective capacities to a high degree. However, so far little is known about how people adapt their tutoring behaviour to robots and whether robots can evoke input that is similar to child-directed interaction. The paper presents detailed analyses of speakers’ linguistic and non-linguistic behaviour, such as action demonstration, in two comparable situations: In one experiment, parents described and explained to their nonverbal infants the use of certain everyday objects; in the other experiment, participants tutored a simulated robot on the same objects. The results, which show considerable differences between the two situations on almost all measures, are discussed in the light of the computer-as-social-actor paradigm and the register hypothesis.
Keywords: human–robot interaction (HRI); social communication; register theory; motionese; robotese; child-directed speech (CDS); motherese; mindless transfer; computers-as-social-actors

Timing Modeling and Analysis for AUTOSAR-Based Software Development - A Case Study - Klobedanz, Kay; Kuznik, Christoph; Thuy, Andre; Müller, Wolfgang (Proceedings of DATE’10, Dresden)
Safety-critical automotive systems must fulfill hard real-time constraints for reliability and safety. This paper presents a case study for the application of an AUTOSAR-based language for timing modeling and analysis. We present and apply the Timing Augmented Description Language (TADL) and demonstrate a methodology for the development of a speed-adaptive steer-by-wire system. We examine the impact of TADL and the methodology on the development process and the suitability and interoperability of the applied tools with respect to the AUTOSAR-based tool chain in the context of our case study.
Keywords: Timing; Programming; Automotive engineering; Application software; Hardware; Computer architecture; Communication system software; Software architecture; Delay; Software standards

RTOS-Aware Refinement for TLM2.0-based HW/SW Design - Becker, Markus; Di Guglielmo, Giuseppe; Fummi, Franco; Müller, Wolfgang; Pravadelli, Graziano; Xie, Tao (Proceedings of DATE’10)
Refinement of untimed TLM models into a timed HW/SW platform is a step by step design process which is a trade-off between timing accuracy of the used models and correct estimation of the final timing performance. The use of an RTOS on the target platform is mandatory in the case real-time properties must be guaranteed. Thus, the question is when the RTOS must be introduced in this step by step refinement process. This paper proposes a four-level RTOS-aware refinement methodology that, starting from an untimed TLM SystemC description of the whole system, progressively introduce HW/SW partitioning, timing, device driver and RTOS functionalities, till to obtain an accurate model of the final platform, where SW tasks run upon an RTOS hosted by QEMU and HW components are modeled by cycle accurate TLM descriptions. Each refinement level allows the designer to estimate more and more accurate timing properties, thus anticipating design decisions without being constrained to leave timing analysis to the final step of the refinement. The effectiveness of the methodology has been evaluated in the design of two complex platforms.
Keywords: Timing; Hardware; Operating systems; Process design; Accuracy; Standards development; Context modeling; Real time systems; Communication channels; Microprogramming

Task Migration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; Defo, Gilles B.; Zabel, Henning; Müller, Wolfgang; Zhi, Yuan
In this paper we present new concepts to resolve ECU (Electronic Control Unit) failures in FlexRay networks. Our approach extends the FlexRay bus schedule by redundant slots with modifications in the communication and slot assignment. We introduce additional backup nodes to replace faulty nodes. To reduce the required memory resources of the backup nodes, we distribute redundant tasks over different nodes and propose the migration of tasks to the backup node at runtime. We investigate different solutions to migrate the redundant tasks to the backup node by time-triggered and event-triggered transmissions.
Keywords: Faulty Node Static Segment Slot Assignment Task Migration Communication Controller

A Novel Uncertainty Decoding Rule With Applications to Transmission Error Robust Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this paper, we derive an uncertainty decoding rule for automatic speech recognition (ASR), which accounts for both corrupted observations and inter-frame correlation. The conditional independence assumption, prevalent in hidden Markov model-based ASR, is relaxed to obtain a clean speech posterior that is conditioned on the complete observed feature vector sequence. This is a more informative posterior than one conditioned only on the current observation. The novel decoding is used to obtain a transmission-error robust remote ASR system, where the speech capturing unit is connected to the decoder via an error-prone communication network. We show how the clean speech posterior can be computed for communication links being characterized by either bit errors or packet loss. Recognition results are presented for both distributed and network speech recognition, where in the latter case common voice-over-IP codecs are employed.
Keywords: automatic speech recognition; bit errors; codecs; communication links; corrupted observations; decoding; distributed speech recognition; error-prone communication network; feature vector sequence; hidden Markov model-based ASR; hidden Markov models; inter-frame correlation; Internet telephony; network speech recognition; packet loss; speech posterior; speech recognition; transmission error robust speech recognition; uncertainty decoding; voice-over-IP codecs

An Inexpensive Packet Loss Compensation Scheme for Distributed Speech Recognition Based on Soft-Features - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2006))
Soft-feature based speech recognition, which is an example of uncertainty decoding, has been proven to be a robust error mitigation method for distributed speech recognition over wireless channels exhibiting bit errors. In this paper we extend this concept to packet-oriented transmissions. The a posteriori probability density function of the lost feature vector, given the closest received neighbours, is computed. In the experiments, the nearest frame repetition, which is shown to be equivalent to the MAP estimate, outperforms the MMSE estimate for long bursts. Taking the variance into account at the speech recognition stage results in superior performance compared to classical schemes using point estimates. A computationally and memory efficient implementation of the proposed packet loss compensation scheme based on table lookup is presented
Keywords: distributed speech recognition; least mean squares methods; MAP estimate; maximum likelihood estimation; MMSE estimate; packet loss compensation scheme; packet switched communication; posteriori probability density function; robust error mitigation method; soft-features; speech recognition; table lookup; voice communication; wireless channels

Profile Management technology for Smart Customization in Private Home Applications - Groppe, Jinghua; Müller, Wolfgang (Proceedings of the 1st International Workshop on Secure and Ubiquitous Networks (SUN-2005))
Smart homes provide their users with maximum comfort and convenience. In this paper, we present a profile management framework for situation-dependent customization in smart home environments, which meet the user preferences with given device capabilities. We apply profile processing and evolution methods to customize profiles on the fly and to automatically evolve user preferences. Furthermore, we give a comprehensive study on profile management technology.
Keywords: Technology management; Smart homes; Environmental management; Resource description framework; Data models; Navigation; Mobile computing; Embedded computing; Ubiquitous computing; Mobile communication

Employment of a multipath receiver structure in a combined GALILEO/UMTS receiver - Bischoff, Renke; Haeb-Umbach, Reinhold; Schulz, Wolfgang; Heinrichs, Guenther (IEEE 55th Vehicular Technology Conference (VTC 2002 Spring))
Current navigation systems like GPS (Global Positioning System) and its Russian counterpart GLONASS (Global Navigation Satellite System) only evaluate the direct signal path. The receivers treat the reflected paths also reaching the receiver antenna as disturbance which has to be suppressed. Multipath affects the tracking accuracy by resulting in a degeneration of the S-curve of the DLL (delay locked loop). Nowadays the future European systems GALILEO and GPSIIF/III with two new signals are on the way to the market and it is time to think about new receiver structures. Therefore we investigated if it is possible to use multipath for navigation constructively.
Keywords: combined GALILEO/UMTS receiver; delay locked loop; delay lock loops; DLL; Global Positioning System; GLONASS; GPS; GPSIIF/III; mobile satellite communication; multipath channels; multipath receiver structure; radio receivers; RAKE receiver; S-curve

Innovative Concepts for Configurating Shared Workspaces through Visual Programming - Dücker, M.; Müller, Wolfgang; Rubart, Jessica (Proceedings of the 32nd Annual Hawaii International Conference on Systems Sciences)
CSCW systems like BSCW (Basic Support for Cooperative Work), HyperNews, and Lotus Notes have been successfully introduced to support the cooperation of geographically distributed work groups. Unfortunately, some of these software systems are not flexible enough to be customized easily to the requirements of an individual user. Most of the environments can only be configured by experts through complex programming. In this article we introduce VIP space, a shared workspace space in the sense of exchanging and processing shared objects between members of distributed work groups. VIP space can be easily adapted to the user's individual views and needs by means of a visual programming language. In VIP space, objects of the shared workspace are moved by drag and drop between task fields. Task fields are programmed by visual "if-then" rules applying a combination of icon- and form-based techniques. When a document represented by an icon is dropped on a task field its rules are checked and actions of the selected rules are excited. VIP space is finally demonstrated in an Internet course application.
Keywords: Application software; Electronic mail; Computer networks; Collaborative work; Teleconferencing; Asynchronous communication; Software systems; Internet; Computer applications; Discussion forums

Agent-Based Modeling for Holonic Manufacturing Systems with Fuzzy Control - Flake, Stephan; Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang; Paelke, Volker (Proceedings of NAFIPS'99, 18th International Conference of the North American Fuzzy Information Processing Society)
Agent-based systems technologies are of emerging interest in the specification and implementation of complex systems. This article introduces the CASA agent development system which seamlessly combines the BDI (belief desire intention) approach with the FIPA agent communication language standard and an integrated specification of fuzzy controllers. The behavior of agents is defined by strategies which basically correspond to extended guarded Horn clauses with priorities. The presented concepts are introduced by an example from computer integrated manufacturing (CIM). The example gives the specification of a fuzzy controller for a manufacturing station in the context of a holonic manufacturing system (HMS).
Keywords: Manufacturing systems; Fuzzy control; Multiagent systems; Control systems; Concurrent computing; Specification languages; Communication standards; Standards development; Communication system control; Computer integrated manufacturing

Transforming SDL Diagrams Into a Complete Visual Representation - Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of Symposium on Visual Languages)
We investigate a translation of SDL diagrams into the complete visual representation of Pictorial Janus (PJ) programs in order to analyze the specification by visual debugging and animation. We additionally introduce timing concepts to PJ (Timed PJ) for a mapping of the SDL timing statements. The concepts transforming SDL interaction and process diagrams into Timed PJ are outlined by an example sketching the transformation of an Ethernet CSMA/CD protocol specification.
Keywords: Animation; Timing; Debugging; Ethernet networks; Multiaccess communication; Protocols; Computer languages; Prototypes; Environmental management; Visualization